Preparation, Spectral Characterization and Antioxidant Activities of Aminothiophene-Containing Schiff Base and Co(II) and Pd(II) Complexes - Colak, Naki; Savci, Ahmet; Turan, Nevin; Buldurun, Kenan (Wiley, 2025)
This research focused on synthesizing a Schiff base (L) and its Co(II) and Pd(II) complexes under appropriate conditions to contribute to enhancing antioxidant activity. The ligand was synthesized by reacting methyl 2-amino-4-ethyl-5-methylthiophene-3-carboxylate with 5-bromo-2-hydroxybenzaldehyde. Various analytical techniques were employed to characterize the ligand and its resulting complexes, including microanalysis, H-1 and C-13 NMR spectroscopy, FTIR, electronic spectra, mass spectrometry, magnetic susceptibility, molar conductance, and thermo-gravimetric analysis. Electronic spectra and magnetic moment values were used to confirm the geometric structures of the synthesized compounds. Thermo-gravimetric analyses (TGA-DTA) were conducted to evaluate the thermal stability of the complexes. The Pd(II) complex was found to have a square planar structure, while a tetrahedral structure was suggested for the Co(II) complex. The results from the elemental analysis were consistent with both the ligand and metal complexes, showing good agreement between calculated and experimental values. The in vitro antioxidant activities of the newly synthesized compounds were examined using different antioxidant methods. Experiment results exhibited that the Pd(II) complex had better activities than the Schiff base and Co(II) complex. According to ABTS experimental results, Pd(II) complex (IC50:1.25) showed similar activity to the standards. In contrast, CUPRAC results revealed that Pd(II) complex (7.55 mu g TE/mL) showed better activity than the standards. The results indicate that Pd(II) complex has strong potential as effective antioxidants, making them valuable for food and medicine applications.
Keywords: ABTS; antioxidant activities; Co(II) and Pd(II) complexes; FRAP; Schiff base